Serotype Distribution of Streptococcus pneumoniae Isolates Causing Invasive and Non-Invasive Infections Using Whole-Genome Sequencing in Ethiopia - Sharew, Bekele (Infect Drug Resist, 2021)
BACKGROUND: In Ethiopia, pneumococcal conjugate vaccine 10 (PCV10) was introduced in 2011 in the national vaccination program. This study was aimed to assess serotype distribution of invasive and non-invasive Streptococcus pneumoniae isolates using whole-genome sequencing. METHODS: A hospital-based prospective study was conducted from 2018 to 2019 at Addis Ababa and Amhara region referral hospitals, from all patients. Clinical Samples were collected and initially cultured onto 5% sheep blood agar at 37°C in a 5% CO(2) atmosphere. Sequencing was done using the Illumina NextSeq 500 and SeroBA was used to predict serotypes from whole-genome sequencing raw data. RESULTS: Of the 57 S. pneumoniae isolates, there were 32 circulating serotypes. The most common serotypes were 15A/B/C (n=5, 8.8%), 6A (n=4, 7.0%), 10A/F (n=4, 7.0%), 23A (n=4, 7.0%) and 7C (n=3, 5.3%). The serotype coverage of PCV10 and PCV13 were 12.3% and 26.3% respectively. The most common invasive serotypes were 15A/B/C (n=5, 8.8%) and 6A (n=4, 7.0%), and non-invasive serotypes were 23A (n=4, 7.0%) and 10A/F (n=3, 5.3%). The most prevalent serotype obtained from PCV10 eligible children was 3 (n=2, 3.5%). The prevalent serotype obtained from PCV10 non-eligible patients were type 23A (n=4, 7%) and type 6A (n=3, 5.2%). The most common serotypes among children ≤18 years old were 10A/F, 7C, 35A/B, 16F, 19A, 3 and 38. However, the proportions of some non-vaccine serotypes (11A/B and 15A/B/C) were higher in adult patients. CONCLUSION: In this study a shift in the distribution of non-vaccinated S. pneumoniae serotypes increases in the population, and PCV10 serotype coverage was reduced as compared to PCV13. Therefore, it is important to continue monitoring serotype changes among all patients in addition to assessing the impact and effectiveness brought by vaccines and provides a foundation for prevention strategies and vaccine policies.